Pine production comparison : production potential of Loblolly pine (Pinus taeda) and Slash pine (Pinus elliottii) in the southeastern USA in relation to initial density and forest management - Ramberg, Åsa (SLU/Dept. of Forest Resource Management, 2019)
The southeastern (SE) United States (US) produces more industrial timber than any other region in the world. Pine plantations in the southern US have increased from 1.8 million acres (728,400 ha) in the beginning of the 1950’s to 32 million acres (13 million ha) in the beginning of the 21st century, and cover 17 % of the forest land. Both the increase in area and productivity over time is remarkable. The increase in productivity is due, in part, to more intensive silviculture methods. Both loblolly and slash pine are being managed intensively in plantations today. In Sweden, another country with large industrial pine timber production, the productivity also has increased over the past 100 years, mainly due to more efficient forest management.